The impact of EU conditionality on human rights situation in Turkey - Yeşilçimen, Aykut (My University, 2008)
Bu çalışmada Türkiye’deki İnsan Haklarının durumu ve AB’nin Türkiye üzerindeki Koşulluluk İlkesi incelenmiştir. İnsan Haklarının durumu yıllara göre incelenmiş ve yıllar arasında kıyaslamalar yapılmıştır. Koşulluluk İlkesinin Türkiye’deki reformlar ve uygulamalardaki etkisi incelenmiştir. Reformların uygulanması, Türkiye’deki bazı davaların incelenmesi ve bunların AİHM uygulamalarıyla olan farklarının belirtilmesi yoluyla ele alınmıştır. Türkiye, reformlarını arttırmış ve hızlandırmıştır. Uygulamada da ilerleme kaydetmiştir. İfade özgürlüğü, işkence ile mücadele, dernek kurma, gösteri ve toplantı özgürlüğü, medya özgürlüğü gibi özgürlükler incelenmiş ve bu konularda Türkiye’nin gelişimi ortaya konmuştur. Ancak, halen Türkiye’de uygulamada bazı eksiklikler mevcuttur, bu eksikler de Türkiye’nin iç dinamiklerinden kaynaklanmaktadır. AB’nin Koşulluluk İlkesi Türkiye’deki reformlarda ve uygulamalarda etkili olmuştur ve demokratikleşmenin önünü açmıştır. Ancak, son yıllarda bu etkisini kaybetmiştir. Bu çalışmada, AB Koşulluluk İlkesinin etkisi incelenmiştir. nsan Hakları, AB Koşulluluk İlkesi, Koşulluluk Etkisinin etkinliği, İnsan Hakları durumu.

In this study, human rights situation in Turkey and the impact of EU conditionality on human rights situation in Turkey is analyzed. Human rights situation in Turkey is examined by looking at the years and some comparisons are made. Then, the impact of EU conditionality on the reforms and implementation is examined. Implementation of reforms is examined through some examples from the applications of European Court of Human Rights and examples from Turkish cases. Accordingly, Turkey made reforms and increased their implementations. Freedom of expression, fight against torture, freedom of setting associations, freedom of demonstrations and meetings and freedom of media were improved through the changes and implementation was also improved through the cases and with references made by the judges to European Convention on Human Rights. However, implementation is still a problem in Turkey because of internal dynamics of Turkey. The EU conditionality is effective and credible on Turkey and in enlargement. Helsinki Summit opened the way of democratization. However, conditionality lost its effect in recent years. In the study, the effectiveness and credibility of the EU conditionality is analyzed. Key Words: Human Rights, EU conditionality, effectiveness of EU conditionality, Human Rights situation.
Keywords: Avrupa Birliği_İnsan Hakları; İnsan Hakları_Türkiye